Early Brain Injury and Adaptive Functioning in Middle Childhood: The Mediating Role of Pragmatic Language. (27th October 2020) - Hendrix, Cassandra L.; King, Tricia Z.; Wise, Justin; Haarbauer-Krupa, Juliet
Abstract: Objective: Traumatic brain injuries (TBIs) often adversely affect adaptive functioning (AF). However, the cognitive mechanisms by which AF is disrupted are not well understood in young children who sustain TBI. This study examined pragmatic language (PL) and executive functioning (EF) as potential mechanisms for AF disruption in children with early, predominantly mild-complicated, TBI. Method: The sample consisted of 76 children between the ages of 6 and 10 years old who sustained a TBI ( n = 36) or orthopedic injury (OI; n = 40) before 6 years of age and at least 1 year prior to testing ( M = 4.86 years, SD = 1.59). Children's performance on a PL and an expressive vocabulary task (which served as a control task), and parent report of child's EF and AF were examined at two time points 1 year apart (i.e., at age 8 and at age 9 years). Results: Injury type (TBI vs. OI) significantly predicted child's social and conceptual, but not practical, AF. Results indicated that PL, and not expressive vocabulary or EF at time 1, mediated the relationship between injury type and both social and conceptual AF at time 2. Conclusions: A TBI during early childhood appears to subtly, but uniquely, disrupt complex language skills (i.e., PL), which in turn may disrupt subsequent social and conceptual AF in middle childhood. Additional longitudinal research that examines different aspects of PL and adaptive outcomes into adolescence is warranted.